Highly wear-resistant ceramic, glaze and method for preparing ceramic products

By using ceramic blanks of components such as kaolin and quartz in ceramic products, and combining ceramic glaze water from materials such as sepiolite to form a porous structure and a high bonding glaze layer, the problem of low glaze strength of ceramic products is solved, and a high wear resistance and smooth and delicate glaze surface is achieved.

CN119143472BActive Publication Date: 2025-03-21FUJIAN DEHUA NEW QILI ARTS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411638074.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-16
Publication Date
2025-03-21
Estimated Expiration
2044-11-16

AI Technical Summary

Technical Problem

The glaze strength of existing ceramic products is not high, and the flatness needs to be improved, making it difficult to meet the needs of high wear resistance.

Method used

Ceramic bodies with kaolin, quartz, carbon fiber powder, cerium oxide and ytterbium oxide are used, and the ceramic glaze layer is formed through specific firing processes and the formula of ceramic glaze water, including sepiolite, styrene-butadiene latex and plasticizers.

Benefits of technology

It achieves high wear resistance of ceramic products, improves glaze strength, and is smooth and delicate, with better performance than traditional products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a high wear-resistant ceramic, glaze and a method for preparing ceramic products, belonging to the technical field of ceramics. The high wear-resistant ceramic comprises a ceramic body and a ceramic glaze layer, the ceramic body comprises the following components: calcined kaolin, quartz, potassium feldspar, sodium feldspar, carbon fiber powder, cerium oxide and ytterbium oxide, the ceramic glaze layer is obtained by coating the ceramic glaze on the surface of the ceramic body and then firing, the ceramic glaze comprises the following components: calcined kaolin, quartz, potassium feldspar, sodium carboxymethyl cellulose, carbon fiber powder, nano molybdenum disilicide, polyvinyl alcohol fiber, fly ash, corundum, sepiolite and cerium oxide. The high wear-resistant ceramic products prepared by the invention have excellent glaze strength, and the glaze is more delicate and shiny.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramics, and in particular relates to a highly wear-resistant ceramic, glaze and a method for preparing a ceramic product. Background Art

[0002] There are more and more ceramic products on the market and they are used in more and more places. Some need to be beautiful, some need to be delicate, and some need to have high wear resistance.

[0003] The Chinese invention patent application document with application number 201510252108.4 discloses a wear-resistant ceramic glaze, in which a variety of sawdust is added to the glaze. During the firing process, a porous structure will be produced on the glaze surface. The glaze strength of the resulting ceramic product is not high, and the glaze flatness needs to be improved.

[0004] Therefore, it is necessary to develop a method for preparing a highly wear-resistant ceramic product. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a highly wear-resistant ceramic, glaze and a method for preparing a ceramic product.

[0006] The present invention adopts the following technical solution:

[0007] A highly wear-resistant ceramic comprises a ceramic body and a ceramic glaze layer attached to the surface of the ceramic body, wherein the ceramic body comprises the following components by mass: 65-71 parts of calcined kaolin, 12-18 parts of quartz, 10-15 parts of potassium feldspar, 10-15 parts of sodium feldspar, 9-11 parts of carbon fiber powder, 13-17 parts of cerium oxide, and 10-14 parts of ytterbium oxide.

[0008] The ceramic glaze layer is obtained by coating ceramic glaze on the surface of the ceramic body and then firing. The ceramic glaze includes the following components by mass: 12 to 17 parts of calcined kaolin, 20 to 26 parts of quartz, 7 to 12 parts of potassium feldspar, 7 to 9 parts of sodium carboxymethyl cellulose, 11 to 15 parts of carbon fiber powder, 8 to 12 parts of nano molybdenum disilicide, 15 to 20 parts of polyvinyl alcohol fiber, 6 to 7 parts of fly ash, 5 to 8 parts of corundum, 9 to 11 parts of sepiolite, and 10 to 14 parts of cerium oxide.

[0009] Furthermore, the method for preparing the ceramic glaze comprises the following steps:

[0010] S1. According to the mass fractions, the carbon fiber powder, nano molybdenum disilicide, polyvinyl alcohol fiber, fly ash, corundum, sepiolite and cerium oxide are mixed and crushed to obtain a primary crushed material, and then the primary crushed material is ball-milled to obtain a primary ball-milled material;

[0011] S2, sieve the primary ball mill material obtained in S1, and dry it at 70-80°C for 30-60min to obtain a modified material;

[0012] S3, according to the mass fractions, mixing and crushing the calcined kaolin, quartz, potassium feldspar and sodium carboxymethyl cellulose to obtain a secondary crushed material, and then performing secondary ball milling on the obtained secondary crushed material to obtain a secondary ball milled material;

[0013] S4, mixing the modified material obtained in S2 and the secondary ball-milled material obtained in S3, adding water, adjusting the Baume degree, and obtaining ceramic glaze water.

[0014] Furthermore, in the process of the first ball milling in S1, the mass ratio of primary crushed material: ball: styrene-butadiene latex: dioctyl phthalate: water = 1:1.2:0.1~0.2:0.1~0.2:1 is adopted, the time of the first ball milling is 12~16h, and the rotation speed of the first ball milling is 500~600r / min.

[0015] Furthermore, in the secondary ball milling process of S3, the mass ratio of secondary crushing material: ball: water is 1:1.1~1.2:1, the time of the secondary ball milling is 10~12h, and the rotation speed of the secondary ball milling is 450~500r / min.

[0016] A method for preparing a highly wear-resistant ceramic product comprises the following specific steps:

[0017] Step 1: Preparation of ceramic body

[0018] The calcined kaolin, quartz, potassium feldspar, sodium feldspar, carbon fiber powder, cerium oxide and ytterbium oxide are mixed according to the mass fraction to obtain a mixture, and then the mixture is ball-milled to obtain a ball-milled material, followed by mud kneading, molding, and drying to obtain a ceramic body;

[0019] Step 2: Glazing and firing

[0020] The ceramic glaze is coated on the surface of the ceramic body obtained in step 1, and then fired and cooled to obtain a highly wear-resistant ceramic product.

[0021] Furthermore, during the ball milling process in step 1, the mass ratio of mixture: ball: water: pore-forming agent is 1:1:1.1-1.2:0.1, the rotation speed of the ball mill is 450-550 r / min, and the ball milling time is 20-24 h.

[0022] Furthermore, the pore-forming agent is one of hawthorn kernel powder or ammonium carbonate.

[0023] Furthermore, the firing process is specifically as follows:

[0024] Raise the temperature to 180-200°C at a heating rate of 0.9-1.0°C / min and keep the temperature constant for 20-30 minutes;

[0025] Heat up to 300-420°C at a heating rate of 0.9-1.0°C / min and keep at constant temperature for 20-30 minutes;

[0026] Heat up to 800-900°C at a heating rate of 1.1-1.3°C / min and keep the temperature constant for 30-40 minutes;

[0027] Raise the temperature to 1250~1300℃ at a heating rate of 1.0~1.2℃ / min and keep the temperature constant for 60~90min;

[0028] Finally, the temperature was lowered to 400-500°C at a cooling rate of 20-30°C / min, and then cooled naturally. Beneficial Effects

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] First, the high wear-resistant ceramic of the present invention uses kaolin as the main skeleton, and is mixed with quartz, carbon fiber powder, cerium oxide and ytterbium oxide. During the ball milling process of the ceramic body, a pore-forming agent is added, and it goes through a specific firing stage: heating to 180-200°C at a heating rate of 0.9-1.0°C / min, keeping the temperature constant for 20-30min, and then heating to 300-420°C at a heating rate of 0.9-1.0°C / min, and keeping the temperature constant for 20-30min. This can effectively form a porous structure in the ceramic body, which not only reduces the weight of the ceramic body, but also effectively provides the strength of the ceramic body.

[0031] Moreover, the porous surface of the green body can improve the adhesion between the glaze layers and further enhance the strength of the glaze layer;

[0032] Second, sepiolite is added to the ceramic glaze, and its water absorption and expansion and adsorption effects are utilized. During the ball milling process, styrene-butadiene latex with adhesive effect and dioctyl phthalate with plasticizing effect are also added. In the one-time ball milling process, the bonding between the various raw materials is effectively improved. In the process of generating bubbles in the ceramic body to form a porous structure, when the bubbles are completely discharged, the glaze raw materials will further fill the defects. After completing the entire firing process, the obtained glaze surface is smooth and the strength is high. High wear-resistant ceramic products. DETAILED DESCRIPTION

[0033] The raw materials used in the present invention are all commercially available products. Example 1

[0034] A highly wear-resistant ceramic, comprising a ceramic body and a ceramic glaze layer attached to the surface of the ceramic body, wherein the ceramic body comprises the following components by mass: 71 parts of calcined kaolin, 18 parts of quartz, 15 parts of potassium feldspar, 15 parts of sodium feldspar, 11 parts of carbon fiber powder, 17 parts of cerium oxide, and 14 parts of ytterbium oxide;

[0035] The ceramic glaze layer is obtained by coating ceramic glaze on the surface of the ceramic body and then firing. The ceramic glaze includes the following components in parts by mass: 17 parts of calcined kaolin, 26 parts of quartz, 12 parts of potassium feldspar, 9 parts of sodium carboxymethyl cellulose, 15 parts of carbon fiber powder, 12 parts of nano molybdenum disilicide, 20 parts of polyvinyl alcohol fiber, 7 parts of fly ash, 8 parts of corundum, 11 parts of sepiolite and 14 parts of cerium oxide.

[0036] The method for preparing ceramic glaze comprises the following steps:

[0037] S1. According to the mass fractions, the carbon fiber powder, nano molybdenum disilicide, polyvinyl alcohol fiber, fly ash, corundum, sepiolite and cerium oxide are mixed and crushed to obtain a primary crushed material, and then the primary crushed material is ball-milled to obtain a primary ball-milled material;

[0038] Wherein, during the first ball milling process, the mass ratio of primary crushed material: ball: styrene-butadiene latex: dioctyl phthalate: water = 1:1.2:0.2:0.2:1 is adopted, the time of the first ball milling is 16h, and the speed of the first ball milling is 600r / min;

[0039] S2, passing the once-milled material obtained in S1 through a 200-mesh sieve, and drying at 80°C for 60 minutes to obtain a modified material;

[0040] S3, according to the mass fractions, calcined kaolin, quartz, potassium feldspar and sodium carboxymethyl cellulose are mixed and crushed to obtain a secondary crushed material, and then the obtained secondary crushed material is subjected to secondary ball milling, and then passed through a 200-mesh sieve to obtain a secondary ball milled material;

[0041] Wherein, during the secondary ball milling process, the mass ratio of secondary crushing material: ball: water: =1:1.2:1 is adopted, the secondary ball milling time is 12h, and the secondary ball milling speed is 450-500r / min;

[0042] S4, mixing the modified material obtained in S2 and the secondary ball-milled material obtained in S3, adding water, and adjusting the Baume degree to 50 to obtain ceramic glaze water.

[0043] A method for preparing a highly wear-resistant ceramic product comprises the following specific steps:

[0044] Step 1: Preparation of ceramic body

[0045] According to the mass fractions, the calcined kaolin, quartz, potassium feldspar, sodium feldspar, carbon fiber powder, cerium oxide and ytterbium oxide are mixed to obtain a mixture, and then the mixture is ball-milled to obtain a ball-milled material, and then passed through a 250-mesh sieve, kneaded, formed, and dried at 80° C. for 24 hours to obtain a ceramic body;

[0046] In the process of ball milling, the mass ratio is mixed material: ball: water: pore-forming agent = 1:1:1.2:0.1, the speed of the ball mill is 550r / min, the time of the ball mill is 24h, and the pore-forming agent is hawthorn kernel powder;

[0047] Step 2: Glazing and firing

[0048] The ceramic glaze is coated on the surface of the ceramic body obtained in step 1, and then fired. The firing process is specifically as follows:

[0049] The temperature was raised to 200°C at a heating rate of 1.0°C / min and kept at this temperature for 30 min;

[0050] The temperature was raised to 420°C at a heating rate of 1.0°C / min and kept constant for 30 min;

[0051] The temperature was raised to 900°C at a heating rate of 1.3°C / min and kept at this temperature for 40 min;

[0052] The temperature was raised to 1300°C at a heating rate of 1.2°C / min and kept constant for 90 min.

[0053] Finally, the temperature was lowered to 500°C at a cooling rate of 30°C / min, and then naturally cooled to obtain a highly wear-resistant ceramic product. Example 2

[0054] A highly wear-resistant ceramic, comprising a ceramic body and a ceramic glaze layer attached to the surface of the ceramic body, wherein the ceramic body comprises the following components by mass: 65 parts of calcined kaolin, 12 parts of quartz, 10 parts of potassium feldspar, 10 parts of sodium feldspar, 9 parts of carbon fiber powder, 13 parts of cerium oxide, and 10 parts of ytterbium oxide;

[0055] The ceramic glaze layer is obtained by coating ceramic glaze on the surface of the ceramic body and then firing. The ceramic glaze includes the following components in parts by mass: 12 parts of calcined kaolin, 20 parts of quartz, 7 parts of potassium feldspar, 7 parts of sodium carboxymethyl cellulose, 11 parts of carbon fiber powder, 8 parts of nano molybdenum disilicide, 15 parts of polyvinyl alcohol fiber, 6 parts of fly ash, 5 parts of corundum, 9 parts of sepiolite and 10 parts of cerium oxide.

[0056] The method for preparing ceramic glaze comprises the following steps:

[0057] S1. According to the mass fractions, the carbon fiber powder, nano molybdenum disilicide, polyvinyl alcohol fiber, fly ash, corundum, sepiolite and cerium oxide are mixed and crushed to obtain a primary crushed material, and then the primary crushed material is ball-milled to obtain a primary ball-milled material;

[0058] Wherein, during the first ball milling process, the mass ratio of primary crushing material: ball: styrene-butadiene latex: dioctyl phthalate: water = 1:1.2:0.1:0.1:1 is adopted, the time of the first ball milling is 12h, and the speed of the first ball milling is 500r / min;

[0059] S2, passing the once-milled material obtained in S1 through a 200-mesh sieve, and drying at a low temperature of 70°C for 30 minutes to obtain a modified material;

[0060] S3, according to the mass fractions, calcined kaolin, quartz, potassium feldspar and sodium carboxymethyl cellulose are mixed and crushed to obtain a secondary crushed material, and then the obtained secondary crushed material is subjected to secondary ball milling, and then passed through a 200-mesh sieve to obtain a secondary ball milled material;

[0061] Wherein, during the secondary ball milling process, the mass ratio of secondary crushing material: ball: water: =1:1.1:1 is adopted, the secondary ball milling time is 10h, and the secondary ball milling speed is 450r / min;

[0062] S4, mixing the modified material obtained in S2 and the secondary ball-milled material obtained in S3, adding water, and adjusting the Baume degree to 45 to obtain ceramic glaze water.

[0063] A method for preparing a highly wear-resistant ceramic product comprises the following specific steps:

[0064] Step 1: Preparation of ceramic body

[0065] According to the mass fractions, the calcined kaolin, quartz, potassium feldspar, sodium feldspar, carbon fiber powder, cerium oxide and ytterbium oxide are mixed to obtain a mixture, and then the mixture is ball-milled to obtain a ball-milled material, and then passed through a 250-mesh sieve, kneaded, formed, and dried at 80° C. for 24 hours to obtain a ceramic body;

[0066] In the process of ball milling, the mass ratio is mixed material: ball: water: pore-forming agent = 1:1:1.1:0.1, the rotation speed of the ball mill is 450 r / min, the ball milling time is 20 h, and the pore-forming agent is ammonium carbonate;

[0067] Step 2: Glazing and firing

[0068] The ceramic glaze is coated on the surface of the ceramic body obtained in step 1, and then fired. The firing process is specifically as follows:

[0069] The temperature was raised to 180°C at a rate of 0.9°C / min and kept constant for 20 min.

[0070] The temperature was raised to 300°C at a heating rate of 0.9°C / min and kept constant for 20 min;

[0071] The temperature was raised to 800°C at a heating rate of 1.1°C / min and kept at this temperature for 30 min;

[0072] The temperature was raised to 1250°C at a heating rate of 1.0°C / min and kept at this temperature for 60 min;

[0073] Finally, the temperature was lowered to 400°C at a cooling rate of 20°C / min, and then naturally cooled to obtain a highly wear-resistant ceramic product. Example 3

[0074] A highly wear-resistant ceramic, comprising a ceramic body and a ceramic glaze layer attached to the surface of the ceramic body, wherein the ceramic body comprises the following components by mass: 68 parts of calcined kaolin, 15 parts of quartz, 13 parts of potassium feldspar, 13 parts of sodium feldspar, 10 parts of carbon fiber powder, 15 parts of cerium oxide, and 12 parts of ytterbium oxide;

[0075] The ceramic glaze layer is obtained by coating ceramic glaze on the surface of the ceramic body and then firing. The ceramic glaze includes the following components in parts by mass: 14 parts of calcined kaolin, 23 parts of quartz, 10 parts of potassium feldspar, 8 parts of sodium carboxymethyl cellulose, 13 parts of carbon fiber powder, 10 parts of nano molybdenum disilicide, 18 parts of polyvinyl alcohol fiber, 6 parts of fly ash, 7 parts of corundum, 10 parts of sepiolite and 12 parts of cerium oxide.

[0076] The method for preparing ceramic glaze comprises the following steps:

[0077] S1. According to the mass fractions, the carbon fiber powder, nano molybdenum disilicide, polyvinyl alcohol fiber, fly ash, corundum, sepiolite and cerium oxide are mixed and crushed to obtain a primary crushed material, and then the primary crushed material is ball-milled to obtain a primary ball-milled material;

[0078] In the process of the first ball milling, the mass ratio of the first crushed material: ball: styrene-butadiene latex: dioctyl phthalate: water = 1:1.2:0.2:0.1:1 is adopted, the time of the first ball milling is 15h, and the speed of the first ball milling is 550r / min;

[0079] S2, passing the once-milled material obtained in S1 through a 200-mesh sieve, and drying at a low temperature of 75°C for 50 minutes to obtain a modified material;

[0080] S3, according to the mass fractions, calcined kaolin, quartz, potassium feldspar and sodium carboxymethyl cellulose are mixed and crushed to obtain a secondary crushed material, and then the obtained secondary crushed material is subjected to secondary ball milling, and then passed through a 200-mesh sieve to obtain a secondary ball milled material;

[0081] Wherein, during the secondary ball milling process, the mass ratio of secondary crushing material: ball: water: =1:1.2:1 is adopted, the secondary ball milling time is 11h, and the secondary ball milling speed is 480r / min;

[0082] S4, mixing the modified material obtained in S2 and the secondary ball-milled material obtained in S3, adding water, and adjusting the Baume degree to 48 to obtain ceramic glaze water.

[0083] A method for preparing a highly wear-resistant ceramic product comprises the following specific steps:

[0084] Step 1: Preparation of ceramic body

[0085] According to the mass fractions, the calcined kaolin, quartz, potassium feldspar, sodium feldspar, carbon fiber powder, cerium oxide and ytterbium oxide are mixed to obtain a mixture, and then the mixture is ball-milled to obtain a ball-milled material, and then passed through a 250-mesh sieve, kneaded, formed, and dried at 80° C. for 24 hours to obtain a ceramic body;

[0086] In the process of ball milling, the mass ratio is mixed material: ball: water: pore-forming agent = 1:1:1.1:0.1, the speed of the ball mill is 500r / min, the time of the ball mill is 22h, and the pore-forming agent is hawthorn kernel powder;

[0087] Step 2: Glazing and firing

[0088] The ceramic glaze is coated on the surface of the ceramic body obtained in step 1, and then fired. The firing process is specifically as follows:

[0089] The temperature was raised to 190°C at a rate of 0.9°C / min and kept constant for 25 min.

[0090] The temperature was raised to 400°C at a heating rate of 1.0°C / min and kept at this temperature for 25 min;

[0091] The temperature was raised to 850°C at a heating rate of 1.2°C / min and kept constant for 35 min.

[0092] The temperature was raised to 1280°C at a heating rate of 1.1°C / min and kept constant for 80 min;

[0093] Finally, the temperature was lowered to 450°C at a cooling rate of 25°C / min, and then naturally cooled to obtain a highly wear-resistant ceramic product.

[0094] Comparison example

[0095] A highly wear-resistant ceramic, comprising a ceramic body and a ceramic glaze layer attached to the surface of the ceramic body, wherein the ceramic body comprises the following components by mass: 68 parts of calcined kaolin, 15 parts of quartz, 13 parts of potassium feldspar, 13 parts of sodium feldspar, 10 parts of carbon fiber powder, 15 parts of cerium oxide, and 12 parts of ytterbium oxide;

[0096] The ceramic glaze layer is obtained by coating ceramic glaze on the surface of the ceramic body and then firing it. The ceramic glaze includes the following components in parts by mass: 14 parts of calcined kaolin, 23 parts of quartz, 10 parts of potassium feldspar, 8 parts of sodium carboxymethyl cellulose, 13 parts of carbon fiber powder, 10 parts of nano molybdenum disilicide, 6 parts of fly ash, 7 parts of corundum, and 12 parts of cerium oxide.

[0097] The method for preparing ceramic glaze comprises the following steps:

[0098] S1. According to the mass fractions, the carbon fiber powder, nano molybdenum disilicide, fly ash, corundum and cerium oxide are mixed and crushed to obtain a primary crushed material, and then the primary crushed material is ball-milled to obtain a primary ball-milled material;

[0099] In the process of the first ball milling, the mass ratio of the first crushed material: the ball: the water is 1:1.2:1, the time of the first ball milling is 15 hours, and the speed of the first ball milling is 550r / min;

[0100] S2, passing the once-milled material obtained in S1 through a 200-mesh sieve, and drying at a low temperature of 75°C for 50 minutes to obtain a modified material;

[0101] S3, according to the mass fractions, calcined kaolin, quartz, potassium feldspar and sodium carboxymethyl cellulose are mixed and crushed to obtain a secondary crushed material, and then the obtained secondary crushed material is subjected to secondary ball milling, and then passed through a 200-mesh sieve to obtain a secondary ball milled material;

[0102] Wherein, during the secondary ball milling process, the mass ratio of secondary crushing material: ball: water: =1:1.2:1 is adopted, the secondary ball milling time is 11h, and the secondary ball milling speed is 480r / min;

[0103] S4, mixing the modified material obtained in S2 and the secondary ball-milled material obtained in S3, adding water, and adjusting the Baume degree to 48 to obtain ceramic glaze water.

[0104] A method for preparing a highly wear-resistant ceramic product comprises the following specific steps:

[0105] Step 1: Preparation of ceramic body

[0106] According to the mass fractions, the calcined kaolin, quartz, potassium feldspar, sodium feldspar, carbon fiber powder, cerium oxide and ytterbium oxide are mixed to obtain a mixture, and then the mixture is ball-milled to obtain a ball-milled material, and then passed through a 250-mesh sieve, kneaded, formed, and dried at 80° C. for 24 hours to obtain a ceramic body;

[0107] During the ball milling process, the mass ratio of mixture: ball: water is 1:1:1.1, the rotation speed of the ball mill is 500 r / min, and the ball milling time is 22 h;

[0108] Step 2: Glazing and firing

[0109] The ceramic glaze is coated on the surface of the ceramic body obtained in step 1, and then the temperature is raised to 1280° C. and fired for 12 hours, and then naturally cooled to obtain a highly wear-resistant ceramic product.

[0110] The high wear-resistant ceramic products obtained in the above three embodiments and the comparative example were tested, wherein:

[0111] The test results are shown in Table 1 below:

[0112] Table 1: Test results

[0113]

[0114] As can be seen from Table 1, the highly wear-resistant ceramic products prepared from Examples 1 to 3 of the present invention have excellent glaze strength, and the glaze is more delicate and glossy, and have better performance than the product prepared in the control example.

[0115] The above is a preferred embodiment of the present invention, and it should be noted that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also considered as the protection scope of the present invention.

Claims

1. A highly wear-resistant ceramic, characterized in that: The ceramic body comprises a ceramic body and a ceramic glaze layer attached to the surface of the ceramic body, wherein the ceramic body comprises the following components by weight: 65-71 parts of calcined kaolin, 12-18 parts of quartz, 10-15 parts of potassium feldspar, 10-15 parts of sodium feldspar, 9-11 parts of carbon fiber powder, 13-17 parts of cerium oxide, and 10-14 parts of ytterbium oxide; The ceramic glaze layer is obtained by coating ceramic glaze on the surface of the ceramic body and then firing it, wherein the ceramic glaze comprises the following components by weight: 12-17 parts of calcined kaolin, 20-26 parts of quartz, 7-12 parts of potassium feldspar, 7-9 parts of sodium carboxymethyl cellulose, 11-15 parts of carbon fiber powder, 8-12 parts of nano molybdenum disilicide, 15-20 parts of polyvinyl alcohol fiber, 6-7 parts of fly ash, 5-8 parts of corundum, 9-11 parts of sepiolite, and 10-14 parts of cerium oxide; The method for preparing the highly wear-resistant ceramic comprises the following specific steps: Step 1: Preparation of ceramic body The calcined kaolin, quartz, potassium feldspar, sodium feldspar, carbon fiber powder, cerium oxide and ytterbium oxide are mixed according to the mass fraction to obtain a mixture, and then the mixture is ball-milled to obtain a ball-milled material, followed by mud kneading, molding, and drying to obtain a ceramic body; Step 2: Glazing and firing The ceramic glaze is applied to the surface of the ceramic body obtained in step 1, and then fired, and cooled to obtain a highly wear-resistant ceramic; The firing process is specifically as follows: Raise the temperature to 180-200°C at a heating rate of 0.9-1.0°C / min and keep the temperature constant for 20-30 minutes; Heat up to 300-420°C at a heating rate of 0.9-1.0°C / min and keep at constant temperature for 20-30 minutes; Raise the temperature to 800-900°C at a heating rate of 1.1-1.3°C / min and keep the temperature constant for 30-40 minutes; Heat up to 1250~1300℃ at a heating rate of 1.0~1.2℃ / min and keep at constant temperature for 60~90min; Finally, the temperature was lowered to 400-500°C at a cooling rate of 20-30°C / min, and then cooled naturally.

2. The highly wear-resistant ceramic according to claim 1, characterized in that: The method for preparing the ceramic glaze comprises the following steps: S1. According to the mass fractions, the carbon fiber powder, nano molybdenum disilicide, polyvinyl alcohol fiber, fly ash, corundum, sepiolite and cerium oxide are mixed and crushed to obtain a primary crushed material, and then the primary crushed material is ball-milled to obtain a primary ball-milled material; S2, sieve the primary ball mill material obtained in S1, and dry it at 70-80°C for 30-60min to obtain a modified material; S3, according to the mass fractions, mixing and crushing the calcined kaolin, quartz, potassium feldspar and sodium carboxymethyl cellulose to obtain a secondary crushed material, and then performing secondary ball milling on the obtained secondary crushed material to obtain a secondary ball milled material; S4, mixing the modified material obtained in S2 and the secondary ball-milled material obtained in S3, adding water, adjusting the Baume degree, and obtaining ceramic glaze water.

3. The highly wear-resistant ceramic according to claim 2, characterized in that: In the process of the first ball milling in S1, the mass ratio of the first crushed material: ball: styrene-butadiene latex: dioctyl phthalate: water = 1:1.2:0.1~0.2:0.1~0.2:1 is adopted, the time of the first ball milling is 12~16h, and the rotation speed of the first ball milling is 500~600r / min.

4. The highly wear-resistant ceramic according to claim 2, characterized in that: In the secondary ball milling process of S3, the mass ratio of secondary crushing material: ball: water is 1:1.1~1.2:1, the time of the secondary ball milling is 10~12h, and the rotation speed of the secondary ball milling is 450~500r / min.

5. The highly wear-resistant ceramic according to claim 1, characterized in that: During the ball milling process in step 1, the mass ratio of mixture: ball: water: pore-forming agent is 1:1:1.1-1.2:0.1, the rotation speed of the ball mill is 450-550 r / min, and the ball milling time is 20-24 h.

6. The highly wear-resistant ceramic according to claim 5, characterized in that: The pore-forming agent is one of hawthorn kernel powder and ammonium carbonate.

Citation Information

Patent Citations

  • Abrasion-resistant ceramic glaze

    CN104860722A

  • Agate glaze and processing method and application thereof

    CN108821797A

  • High strength antifouling tile and preparation method of same

    CN109020481A

  • Wear-resistance and heat-resistance functional ceramic pot and preparing technology thereof

    CN109608166A